Supervision of the Development of Higher-Order Thinking Skills (HOTS)-Based Assessment of Learning in Wijaya Putra School: Supervisi Penyusunan Assessment of Learning Berbasis HOTS di SMA Wijaya Putra Surabaya - Setyowati, Yulis; Priambudi, Surya; Dewanto, Dewanto (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
As an educator, a teacher ideally should have a strong understanding of the concept of Higher Order Thinking Skills (HOTS) in learning and assessment. This understanding is crucial to support the implementation of teaching and assessment in the era of Society 5.0. Higher Order Thinking Skills, commonly known as HOTS, refer to an individual's ability to think in a more complex manner. Indicators used in HOTS questions include three aspects within the context of Bloom's taxonomy, namely analysis (C4), evaluation (C5), and creation (C6). This community service activity aims to illustrate the steps and analyze the results of supervision in enhancing the competence of teachers in developing HOTS-based learning assessments at SMA Wijaya Putra in Surabaya. The supervision method employed is participative, utilizing direct guidance and Focus Group Discussions. The results of this supervision show an improvement in teachers' ability to create assessments of learning.This improvement is evident in the initial observation of learning assessments, where only ability increased to 75%, indicating a substantial improvement from the initial condition. In conclusion, this community service activity successfully enhanced the skills of teachers in developing HOTS-based assessments.".